Finance, Inequality, and Poverty: Cross-Country Evidence - Beck, Thorsten; Demirguc-Kunt, Asli; Levine, Ross (World Bank, Washington, DC, 2013)
While substantial research finds that financial development boosts overall economic growth, the authors study whether financial development is pro-poor: Does financial development disproportionately raise the income of the poor? Using a broad cross-country sample, the authors find that the answer is yes: Financial intermediary development reduces income inequality by disproportionately boosting the income of the poor and therefore reduces poverty. This result is robust to controlling for simultaneity bias and reverse causation.